The rare deep-living hyperiid amphipod Megalanceoloides remipes (Barnard, 1932): complementary description and symbiosis - Gasca, Rebeca; Haddock, Steven H.d. (Zootaxa, 2016)
A female ovigerous specimen of the rare deep-living hyperiid Megalanceoloides remipes (Barnard, 1932) was collected with a remotely operated submersible (ROV) at a depth of 2,094 m in the Farallon Basin, Gulf of California. The specimen was found to be symbiotically associated with the siphonophore Apolemia sp. Eschscholtz, 1829. Hitherto, this species was known only from two other specimens, one from the South Atlantic and another from the Indian Ocean; the present record is the first from the Pacific Ocean. Previous descriptions lacked morphological details of different appendages; these data are provided here. In addition, we present the first data on its symbiotic association from in situ observations. The colors of the hyperiid and of some parts of the Apolemid were very similar, thus supporting the notion that some hyperiids tend to mimic the color of its host.